2000
DOI: 10.1097/00004770-200010000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Association of Putative Pathogens in Root Canal Infection

Abstract: The purpose of this study was to investigate the epidemiology of putative pathogens in root canals with apical periodontitis and to determine the associations among the putative pathogens. Eighteen symptomatic and 20 asymptomatic teeth from 36 subjects were studied. This research was performed with polymerase chain reaction and hybridization using rRNA-based oligonucleotide probes. The most frequently found species was Fusobacterium sp. (68.4%), followed by Peptostreptococcus micros (44.7%) and Porphyromonas g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
13

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 19 publications
7
70
0
13
Order By: Relevance
“…The Effect of Treponema denticola immunoinhibitory protein on cytokine expression in T cells Treponema denticola have been rarely found associated with endodontic diseases, however, unidentified spirochete species have now been found in endodontic infections by employing polymerase chain reaction (PCR) method 6,[15][16][17] . In this regard, Smallwood et al 18) recently reported the occurrence of spirochetes in all samples collected from infected canals using PCR.…”
Section: ⅲ Resultsmentioning
confidence: 99%
“…The Effect of Treponema denticola immunoinhibitory protein on cytokine expression in T cells Treponema denticola have been rarely found associated with endodontic diseases, however, unidentified spirochete species have now been found in endodontic infections by employing polymerase chain reaction (PCR) method 6,[15][16][17] . In this regard, Smallwood et al 18) recently reported the occurrence of spirochetes in all samples collected from infected canals using PCR.…”
Section: ⅲ Resultsmentioning
confidence: 99%
“…Siqueira, et al hanno dimostrato che T. denticola è associata alla presenza di ascessi di origine endodontica, con una positività del 79% (22). Jung, et al, invece non hanno trovato alcuna correlazione tra T. denticola e sintomi clinici (11). Studi precedenti hanno ipotizzato inoltre che T. denticola potrebbe essere coinvolto nella differenziazione degli osteoclasti durante le infezioni endodontiche, a causa dei fattori di virulenza di cui è dotata (2,5).…”
Section: Discussioneunclassified
“…Literatür bilgilerine göre, oral mikroflorada 300 ile 500 arasında bakteri türü bulunmaktadır. 2,3 Ancak, bunlardan sadece bir kısmı (150 civarında) pulpaya çeşitli yollarla (koronal, retrograd veya hematojen) girerek, pulpa hastalıklarına neden olabilmektedir. [4][5][6][7][8][9] Kök kanalındaki bu bakteriler 10-12 çeşit genustan oluşmaktadır.…”
Section: Kök Kanallarında Mikroorganizmalarunclassified